Analisis Institutional Ownership, Managerial Ownersip dan Capital Structure - Efrinal -; Ayu Ning Tias (AKRUAL : Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of institutional ownership and managerial ownership on the capital structure of transportation companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample in this study amounted to 100 companies in the transportation sub-sector companies listed on the Indonesia Stock Exchange for 5 (five) years using the purposive sampling method. This study used secondary data. The data analysis technique used in this study is Multiple Linear Remotion Analysis with the regression equation Y = -1.302 + 0.789X1 + 0.203X2 + 0.208X3. The results of this study show that institutional ownership has no significant effect on the capital structure. Meanwhile, managerial ownership has a positive and significant effect on the capital structure.